Genetic confirmation of Octopus insularis (Leite and Haimovici, 2008) in South Florida, United States using physical features and de novo genome assembly - Maloney, Brigid; Ramos, Eric Angel; Bennice, Chelsea O.; Young, Frank; Magnasco, Marcelo O. (Frontiers in Physiology, 2023)
The distribution of octopuses within the Octopus vulgaris species complex remains inadequately understood. Species determination can be complex and involves characterizing a specimen's physical features and comparing its genetic makeup to other populations. In this study, we present the first genetic confirmation of Octopus insularis (Leite and Haimovici, 2008) inhabiting the coastal waters of the Florida Keys, USA. We employed visual observations to identify species-specific body patterns of three wild-caught octopuses and used de novo genome assembly to confirm their species. All three specimens exhibited a red/white reticulated pattern on their ventral arm surface. Two specimens displayed body pattern components of deimatic display (white eye encircled by a light ring, with darkening around the eye). All visual observations were consistent with distinguishing features of O. insularis. We then compared mitochondrial subunits COI, COIII, and 16S in these specimens across all available annotated octopod sequences, including Sepia apama (Gray, 1849) as a control outgroup taxon. For species exhibiting intraspecific genomic variation, we included multiple sequences from geographically distinct populations. Laboratory specimens consistently clustered into a single taxonomic node with O. insularis. These findings confirm O. insularis presence in South Florida and suggest a more extensive northern distribution than previously assumed. Whole genome Illumina sequencing of multiple specimens enabled taxonomic identification with well-established DNA barcodes while also generating the first de novo full assembly of O. insularis. Furthermore, constructing and comparing phylogenetic trees for multiple conserved genes is essential for confirming the presence and delineation of cryptic species in the Caribbean.